Harlan County USA - Kopple, Barbara (United States, 1976)
Barbara Kopple’s Academy Award–winning Harlan County USA unflinchingly documents a grueling coal miners’ strike in a small Kentucky town. With unprecedented access, Kopple and her crew captured the miners’ sometimes violent struggles with strikebreakers, local police, and company thugs. Featuring a haunting soundtrack—with legendary country and bluegrass artists Hazel Dickens, Merle Travis, Sarah Gunning, and Florence Reece—the film is a record of the thirteen-month struggle between a community fighting to survive and a corporation dedicated to the bottom line. (criterion)
Keywords: Documentary films